Perforated multicentric adenocarcinoma of the small bowel. - Sarroca, Carlos; Valls, Alberto; de los Santos, Julio; di Leoni, Francisco (Cirugía del Uruguay, 1976)
A brief clinical and pathological review of the adenocarcinomas of the small bowel is made, pointing out the most important synthoms and signs. A contribution is made to the National Series of a new case of primitive adenocarcinoma of the small bowel, which stands out for being multicentric and manifesting itself by peritonitis, due to tumoral perforation.